Ischemic dilated cardiomyopathy complicating Tetralogy of Fallot. Issue 2 (February 2021) - Spiniello, Giorgio; Scognamiglio, Giancarlo; Merola, Assunta; Palma, Michela; Fusco, Flavia; Sarubbi, Berardo
Abstract : Supplemental Digital Content is available in the text